Adultery as a Complaint Offense in Overcoming Free Sex Behavior - Topan, Muhammad (International Journal of Law, Environment, and Natural Resources, 2023)
Globalization has a global meaning which is likened to freedom. Many foreign cultures have entered, even though these cultures are not in accordance with our Eastern culture. For example, the culture of free sex behavior that is widespread in Western culture is not to our culture and is contrary to the foundation of our country, Pancasila. Indonesia has six officially recognized religions, namely Islam, Protestant Christianity, Catholic Christianity, Hinduism, Buddhism, and Confucianism. The majority of official religions in Indonesia give the view that free sex is a deviant behavior. The opening of the 1945 Constitution in the third paragraph states that it is the grace of God Almighty and so on. That is, this view has juridical consequences for all laws and regulations which must refer to and originate from theological values, namely the value of Belief in the One and Only God. With the expansion of the offense of adultery in the new Criminal Code that "adultery for men and women who are not married (not legally married) can also be punished", meaning that the new Criminal Code has referred to and sourced theological values ??as a basis for expanding the meaning of adultery, namely by the principle of Belief in the One and Only God in Pancasila. However, the formulation of complaint offenses in the new Criminal Code which limits only family members who can complain needs to be reviewed again for a criminal law policy in the context of tackling free sex behavior which is currently engulfing Indonesian society. Because by being limited to only the family who can complain, this is of course the same as opening up the family's disgrace, so there is a possibility that there will be no complaints. In addition, it is not right to limit only family members who can make complaints because they are considered the victims who are most affected. So actually it can also be assessed that the most affected by this free-sex behavior is not only the family but it must be interpreted that there is a "society" (or "community morals") as victims. When viewed in the context of collective morality, society suffers greatly because the quality of life together has decreased in quality or is referred to as moral degradation.